2015
DOI: 10.1371/journal.pone.0134737
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Kidney Transplant Patients Due to Escherichia coli and Klebsiella pneumoniae-Producing Extended-Spectrum β-Lactamases: Risk Factors and Molecular Epidemiology

Abstract: Urinary tract infection (UTI) is a common complication after kidney transplantation, often associated to graft loss and increased healthcare costs. Kidney transplant patients (KTPs) are particularly susceptible to infection by Enterobacteriaceae-producing extended-spectrum β-lactamases (ESBLs). A retrospective case-control study was conducted to identify independent risk factors for ESBL-producing Escherichia coli and Klebsiella pneumoniae in non-hospitalized KTPs with UTI. Forty-nine patients suffering from U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
2
33
2
1
Order By: Relevance
“…Again, our sample size precluded an examination of specific prophylactic agents. Consistent with other studies, 66% of subsequent isolates were concordant with the index isolates (9,11,12). This finding suggests a persistent reservoir of resistant bacteria, likely in the gastrointestinal tract or the genitourinary tract, which was not eliminated during the treatment of the preceding infection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Again, our sample size precluded an examination of specific prophylactic agents. Consistent with other studies, 66% of subsequent isolates were concordant with the index isolates (9,11,12). This finding suggests a persistent reservoir of resistant bacteria, likely in the gastrointestinal tract or the genitourinary tract, which was not eliminated during the treatment of the preceding infection.…”
Section: Discussionsupporting
confidence: 88%
“…Reported rates of subsequent ESC-R infections range between 16% and 45% (7)(8)(9)(10)(11), but few studies have evaluated potential risk factors for subsequent ESC-R infections (9,12). In our prior single-center study, we identified the receipt of Ն14 days of antibiotics in the previous 91 days as an independent predictor for subsequent ESC-R urinary tract infection (UTI) in children.…”
mentioning
confidence: 99%
“…38 , 39 Bacteria from the family Enterobacteriaceae , particularly Escherichia coli , have been associated with increased systemic lipopolysaccharides 136 , increased risk of obesity, inflammation, reduced glomerular filtration rate, increased serum cystatin C and insulin resistance. 71 , 137 , 138 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of urinary tract infections is approximately 5% to 36% and may reach up to a 60% during the first year after transplant. 1,2 Immunosuppressive medications are the major causes of infections among organ transplant recipients. 3 Early diagnosis of urinary infections improves long-term graft survival.…”
Section: Introductionmentioning
confidence: 99%